1996
DOI: 10.1093/aesa/89.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differentiation of Alfalfa Weevil Strains (Coleoptera: Curculionidae)

Abstract: Mitochondrial DNA was amplified and sequenced from eastern, western, and Egyptian strains of alfalfa weevil, Hypera postica (Gyllenhal). Eastern and Egyptian weevils differed at only 2 nucleotide sites in 1,031 base pairs sequenced; western weevils differed by 5% sequence divergence. Three restriction sites were identified which separated eastern and western haplotypes. No intrastrain polymorphism was detected in 150 weevils from Nebraska. Collections from Lincoln in eastern Nebraska and Scottsbluff in western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
60
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 16 publications
0
60
3
Order By: Relevance
“…Issues related to different strains and their biology may also contribute to differences in degree-days. Ongoing research suggests the eastern strain has been replaced by the western strain of the alfalfa weevil in northern Nebraska (Erney et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues related to different strains and their biology may also contribute to differences in degree-days. Ongoing research suggests the eastern strain has been replaced by the western strain of the alfalfa weevil in northern Nebraska (Erney et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The western strain was introduced into the Salt Lake City, UT, area in 1904 (Hamlin et al 1949), and the eastern strain was introduced into Maryland in 1952 (White et al 1972, Erney et al 1996.…”
mentioning
confidence: 99%
“…Because only three WCR and two MCR were sequenced, we remain very cautious about claiming that the two site polymorphisms are diagnostic. Low levels of genetic diversity in the ITS1 and mtDNA regions among widely dispersed populations have been reported for other insect species including European corn borer, Ostrinia nubilalis (Marcon et al ., 1999), stable fly, Stomoxys calcitrans , tobacco budworm, Heliothis virescens (Roehrdanz et al ., 1994), monarch butterfly, Danaus plexippus (Brower & Boyce, 1991), gypsy moth, Lymanatria dispar (Bogdanowicz et al ., 1993) and alfalfa weevil, Hypera postica (Erney et al ., 1996). These species have high mobility or recent expansion from a genetic bottleneck in common.…”
Section: Discussionmentioning
confidence: 99%
“…Allozyme and genetic analyses now suggest that the western strain is possibly a separate species from the more closely related eastern and Egyptian strains Stutz 1985, Erney et al 1996). Morphological differences seem to be of little value (Erney et al 1996). However, certain behavioral, ecological, and physiological differences seem to aid in identiÞcation.…”
mentioning
confidence: 99%
“…However, these techniques could still not separate eastern from Egyptian strains. Erney et al (1996) sequenced mitochondrial DNA from each strain and found diagnostic restriction sites for separating eastern and Egyptian strains from western. Eastern and Egyptian weevils varied at only two nucleotide sites of Ͼ1000 sequenced base pairs and could not be separated by use of restriction enzymes, but they could be identiÞed by sequencing mitochondrial DNA.…”
mentioning
confidence: 99%